Formulation and evaluation of almotriptan chewable tablets - V. Anil kumar; K.L. Deepthi; R. Kalyani; B. Padmasri; D.Prasanth (International Journal of Pharmacy and Analytical Research, 2016)
In the present work, Almotriptan chewable tablets were prepared. All the tablets were subjected to weight variation, drug content uniformity, lock length, dissolution, drug excipients interaction and short-term stability studies. There was no difference in the position of the absorption bands, hence providing evidence for the absence o f any chemical incompatibility between pure drugs with the excipients. The bulk density and tapped density for all formulation (F1 – F9) varied from 0.423 - 0.485 gm/cm3 and 0.501 - 0.593 gm/cm3 respectively. The results of carr’s consolidate index or % compressibility index and hausner’s ratio for the entire formulation (F1 – F9) blend range from 15.5- 19.1 and 1.10-1.28 respectively, shows fair flow properties. All the tablets show similar color, odour, taste and physical appearance. There is no impact of different in their organoleptic properties. By using the different excipient, the hardness values ranged from 3.0-3.5 kg/cm2 for formulations (F1-F9) .The entire tablet passes weight variation test, as the average % weight variation was within the Pharmacopeial limit - 7.5%. It was found to be 149mg - 152 mg. The weight of all the tablets was found to be uniform with less deviation. The concentration of the drug in all the formulations with different polymers was found to be 97.35 – 99.58%. It was within the IP limits. In the present work, Almotriptan chewable tablets were prepared. All the tablets were subjected to weight variation, drug content uniformity, lock length, dissolution, drug excipients interaction and short-term stability studies. There was no difference in the position of the absorption bands, hence providing evidence for the absence o f any chemical incompatibility between pure drugs with the excipients. The bulk density and tapped density for all formulation (F1 – F9) varied from 0.423 - 0.485 gm/cm3 and 0.501 - 0.593 gm/cm3 respectively. The results of carr’s consolidate index or % compressibility index and hausner’s ratio for the entire formulation (F1 – F9) blend range from 15.5- 19.1 and 1.10-1.28 respectively, shows fair flow properties. All the tablets show similar color, odour, taste and physical appearance. There is no impact of different in their organoleptic properties. By using the different excipient, the hardness values ranged from 3.0-3.5 kg/cm2 for formulations (F1-F9) .The entire tablet passes weight variation test, as the average % weight variation was within the Pharmacopeial limit - 7.5%. It was found to be 149mg - 152 mg. The weight of all the tablets was found to be uniform with less deviation. The concentration of the drug in all the formulations with different polymers was found to be 97.35 – 99.58%. It was within the IP limits.